Metode dan Etika Mencari Ilmu dalam Perspektif Islam - Nuruddien, Muhammad; Ahmad, Muhammad Ghazali; Rumaisya; Abbas, Ngatmin (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2024)
This study discusses the methods and ethics of seeking knowledge in Islam based on the perspective of hadith. Seeking knowledge holds a crucial position in Islamic teachings, where the Prophet Muhammad emphasized the importance of knowledge and the manners associated with it. The hadiths related to seeking knowledge provide guidance on the proper way to acquire knowledge, including the ethics that must be observed by a student. This research employs a qualitative approach using literature review methods of hadiths related to the pursuit of knowledge. Primary data sources are derived from authentic hadith collections such as Sahih Bukhari and Sahih Muslim, as well as interpretations from scholars, then the data that has been collected is analyzed by thematic analysis method. The results show that the method of seeking knowledge in Islam should be based on sincere intentions, humility, and patience. Additionally, students must respect their teachers, maintain proper ethics during the learning process, and practice the knowledge they gain. This study also highlights that the ethics taught by Prophet Muhammad in seeking knowledge are relevant in the context of modern education. In conclusion, the hadiths provide comprehensive guidance for building character and manners in the pursuit of knowledge.